Air-side performance analysis of a wire-on-tube heat exchanger with an oscillating heat pipe as an extended surface under natural convection conditions - Samana T. (2017)
This study investigates the performance of a wire-on-tube heat exchanger that uses an oscillating heat pipe as an extended surface under natural convection. The results have been compared with those of a conventional wire-on-tube unit. The heat exchanger exchanges heat between hot water flowing inside the tube, which is varied from 50 to 85°C, and the surrounding ambient air, which is kept constant at 25°C. The tested unit is installed in the horizontal and vertical directions, and the effects of tube diameter and tube and wire pitches on thermal performance are considered. The results show that the performance of the heat exchanger with an oscillating heat pipe is slightly higher than that of the conventional wire-on-tube heat exchanger. It was also found that the air-side performance of the heat exchanger is directly proportional to the tube diameter and tube and wire pitches. Moreover, when the heat exchanger is installed horizontally, its performance is approximately 15-20% higher than that of the unit in the vertical installation. A heat transfer model for evaluating the heat exchanger performance is also developed, and the results agree well with the experimental data. © 2012 Copyright Taylor and Francis Group, LLC.